Loudness dependence of the auditory evoked potential: temporal stability, associations to sociodemographic variables, and functional significance—implications for clinical research - Andersson, Stein; Rygvold, Trine Waage; Hatlestad-Hall, Christoffer (Frontiers in Human Neuroscience, 2025)
IntroductionThe loudness dependence of the auditory evoked potential (LDAEP) has been suggested as a biomarker for central serotonergic function, and as such a proxy for serotonin related psychiatric symptomatology and intervention outcome, particularly in depression. This study aims to explore LDAEP characteristics in a large healthy population by assessing its test–retest reliability and examining associations with sociodemographic variables, psychological distress, and performance-based cognitive function.MethodsOur sample included 100 healthy adults whose LDAEP was measured and correlated with age, sex, self-reported psychological distress, and cognitive performance.ResultsParticipants examined twice (n = 38) showed high test-retest reliability with intraclass correlations (ICCs) between 0.67 and 0.89 over a 2-to-3-month interval. Furthermore, the magnitude of the LDAEP was significantly higher in women than men, and female hormonal contraceptive users exhibited higher LDAEP than non-users. In females, age was inversely correlated with LDAEP. However, no significant associations were found between LDAEP and measures of psychological distress, including depressive symptoms, nor with cognitive test performance.DiscussionThese results underline LDAEP's reliability as a biomarker over time, but also highlight age, sex and hormonal contraceptive use as significant factors influencing the LDAEP. Future research in clinical population should take these results into account, with an emphasis on providing the necessary sample sizes for relevant sub-group analyses.